Palmares, palmeira: esquadrinhando a resistência das vozes do sul na Pequena Angola - Lopes, Wanderlei de Sousa (2023)
The purpose of this study is to understand the meaning-making process of the comic book Angola Janga: kingdom of runaway slaves, by Marcelo D’Salete, a fictional work, but of extensive research on the bibliographies alluding to the conflicts of the Quilombos dos Palmares, in the late of centuries XVI and XVII, and early of XVIII. From the mixture between fiction and historicity, D’Salete tells his version of Palmares, with an emphasis on black voices and culture. For the purpose of this research, we base ourselves on the french/greimasian semiotic theory, which has the text (taken holistically) as its object of study, aiming to highlight its conditions of apprehension and production of meaning. Furthermore, taking into account the theme of Angola Janga and that it is part of the collection of books purchased by programs to encourage reading in Brazilian public schools, the work meets the ideals proposed by Moita Lopes (2016) about the current role of Applied Linguistics. The methodology used is qualitative, bibliographical, descriptive and interpretive. We hope to contribute to the process of understanding and apprehending the meaning of our object of study, as well as contributing to the deepening of validation of knowledge of minorities.